Damned if You Do, Damned if You Don't? Experimental Evidence from Germany on Hiring Discrimination Against Mothers with Short Family Leave - Lena Hipp (Work and Occupations, 2025)
Can women overcome motherhood penalties by quickly returning to their jobs after childbirth? Do employers discriminate against fathers who take extended family leave? To answer these questions, I exploit some unique features of Germany's parental leave and job application system. My field experiment shows that mothers who only took the mandatory leave of two months are less likely to be invited to a job interview than mothers who stayed home for a year. There is, however, no difference between fathers who took short versus long periods of leave. The results of the supplementary laboratory experiment support my theoretical claim that women who “lean in” and violate the norm of being “a good mother” are judged more negatively than norm-violating men, who benefit from their culturally ascribed higher status in professional settings. My study hence underscores that women are required to enact traditional family roles to “fit in” but men are not. Fathers have more leeway in their behaviors and are evaluated according to a more flexible range of criteria than mothers.
Keywords: 300; gender; parenthood; family leave; discrimination; field/laboratory experiment